Photocatalytic Reduction of Cu(II) Ion and TiO2-Catalyzed Paracetamol Photodegradation As An Alternative Method in Waste Treatment - Devina Ingrid Anggraini; Eka Susanti Hp; Erliena Okta Guna Santosa (UNIVERSITAS SEBELAS MARET (UNS), 2015)
Recently, the issue of heavy metals are wastes is become popular such as Cu, Co, Pb, and etc. Furthermore, the presence of Cu together with paracetamol as pharmacy waste. Photocatalytic process could be an alternative to avoid the situation. This research investigated the influence of irradiation and the initial concentration of paracetamol toward TiO2-catalyzed photoreduction of Cu(II). The research aims to develop a photoreduction method that is catalyzed by TiO2 in the presence of paracetamol in reducing Cu(II) and paracetamol concentration. Cu(II) photoreduction process was (II) conducted in a close reactor equipped with a UV lamp. The remaining Cu(II) in solution was analyzed using Atomic Absorption Spectrophotometry (AAS) to determine its concentration and paracetamol concentration by visible spectrophotometry method. Results showed that the use of photocatalyst TiO2improves the photoreduction of Cu(II), 15-45 minutes irradiation also contributes the increment, over the time a tiny decrease in photoreduction effectivity occur, however. At initial paracetamol concentration, 50 to 250 mg/L lead to an increase in photodegradation of paracetamol, and large decline occur over e.i. 250 mg/L, however. The presence of paracetamol may increase the effectiveness of Cu(II) photoreduction due to the prevention of radical OH• and electrons recombination. The most effective photoreduction of 25 mL solution of ion Cu(II) 10 mg/L is readily achieve in reaction conditions using 20 mg of TiO2 by 45 minutes irradiation in the present of 25 mL of paracetamol 250 mg/L. By those Cu(II) ion was reduced by 98.87 % and 14.73 % of paracetamol was degraded.